The impact of submesoscale frontogenesis on microscale turbulence in the Tsushima Warm Current - Ito, Daiki; Kawaguchi, Yusuke; Wagawa, Taku; Yabe, Itsuka (Frontiers in Marine Science, 2025)
The process of submesoscale frontogenesis within the Tsushima Warm Current (TWC) front, and the enhancement of the microscale turbulence associated with this frontogenesis, was examined using in situ observational data. Multiple sections across the front captured deformation flow on the western side of the southward-flowing meander crest from the main axis of the TWC front. The frontogenesis was caused by deformation within the observed area. Submesoscale patches encompassing different water masses were found near the growing front. Observation of microstructure revealed that the turbulent dissipation rates and the vertical diffusivity were relatively large near the area of strong deformation flow and patchy structure. This turbulence is attributed to frontogenesis and the patchy pattern of the water mass. The estimation of the vertical buoyancy flux and the resulted energy conversion revealed that only a few percent of the energy supplied by the ageostrophic secondary circulation needs to cascade into turbulence to account for the observed turbulent dissipation. The results indicate that the submesoscale frontogenesis and the resulting submesoscale water mass patterns, which are ubiquitous over the global ocean, contribute to the turbulent mixing and consequently to the effective energy cascade.